“I had post-concert depression”: A study of Lucy fans after the Jakarta concert - Ramadhiansyah, Dimas (Program Studi Ilmu Komunikasi, 2025)
This study examines the impact of Hallyu, particularly K-pop, on fan communities in Indonesia, focusing on the phenomenon of Post-Concert Depression (PCD) often experienced by fans after major concerts. Using the netnography method, the study observes the interaction dynamics within a WhatsApp group of LUCY fans following the